2016
DOI: 10.1007/s11743-016-1812-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activities of Three Anionic Gemini Surfactants Derived from Cyanuric Chloride: Effect of a Branched Hydrophobic Chain

Abstract: Sodium 4,6-(2-(N,N-bis-ethylhexylamino)-1,3,5-triazine-4,6-yl-amino) ethane sulfonate (IXC 8 ), Sodium 4,6-(2-(N,N-bis-octylamino)-1,3,5-Triazine-4,6-ylamino) ethane sulfonate (XC 8 ) and 2,2 0 -(6,6 0 -(ethane-1,2diylbis(azanediyl) bis(4-(octylamino)-1,3,5-triazine-6,2diyl)) bis(azanediyl))diethane sulfonate (C 8 -2-C 8 ) were synthesized from cyanuric chloride. The surface activity and application properties of these surfactants (XC 8 , IXC 8 and C 8 -2-C 8 ) were discussed. The values of CMC, c CMC , pC 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This means that the synthesized 3C n taDA have weak emulsifying power, and that they cannot be used as emulsifiers. This result is in accordance with those of other oligomeric surfactants (Hu et al, 2016;Tai et al, 2012;Xu et al, 2015).…”
Section: Emulsion Stabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…This means that the synthesized 3C n taDA have weak emulsifying power, and that they cannot be used as emulsifiers. This result is in accordance with those of other oligomeric surfactants (Hu et al, 2016;Tai et al, 2012;Xu et al, 2015).…”
Section: Emulsion Stabilitysupporting
confidence: 92%
“…Emulsification is one of the most important surface properties of the surfactants at the interface. There are two main factors, the low surface tension and high mechanical strength of the interfacial film, which determines emulsion ability (Hu et al, ). To some extent, the latter is more import.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that surfactants with branched hydrophobic groups have higher CAC values than the corresponding straight-chain ones [ 56 ]. It was stated that branched hydrocarbon chains have weaker intermolecular cohesive forces than those of the straight ones [ 57 ]. Moreover, surfactants with bulky hydrophobic groups were shown to have higher CAC than similar but less bulky surfactants due to difficulties with the incorporation of these groups into the micelle [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that another index will be better to describe the effect of the structure on critical micelle concentration of cationic (chloride) gemini surfactants. Because some experimental data show that the branched chains especially branched hydrocarbon chains [17, 23, 27], and also heteroatoms [2426], cause the higher cmc values therefore the best index which will satisfactorilydescribe the effect of the chemical structure on cmc value is the first-order valence molecular connectivity index ( 1 χ ν ). The first-order valence molecular connectivity index ( 1 χ ν ) is similar to the first-order molecular connectivity index ( 1 χ ), but it includes heteroatom information.The values of 1 χ ν index increase with the increase in length of hydrocarbon chains, and its values decrease with the increase in branches.…”
Section: Resultsmentioning
confidence: 99%